Methamphetamine and cardiac disease among people with HIV infection. Issue 10 (1st August 2020) - Martin, TCS; Gianella, S; Franklin, D; Hsue, P; Smith, DM
Abstract : Objectives: People living with HIV (PWH) are at elevated risk of cardiac disease compared to the general population. Methamphetamine use has been associated with structural heart disease and increased mortality from cardiovascular disease but has not been explored as a cause of cardiac disease among PWH. We sought to evaluate the association of methamphetamine use and cardiac disease among PWH. Methods: We performed a case–control study of participant data in the HIV Neurobehavioral Research Program. Cases were defined as PWH with a history of myocardial infarction or a history of heart failure (systolic or diastolic). Covariates, including methamphetamine abuse/dependence, were assessed using multiple logistic regression. Results: Among 3747 PWH, there was a history of myocardial infarction in 115 subjects (3.1%), and a history of heart failure in 41 (1.1%). Current or prior methamphetamine abuse/dependence was reported in 1036 (27.9%) and was not associated with myocardial infarction ( P = 0.27) or heart failure ( P = 0.84). In addition to traditional risk factors, variables associated with myocardial infarction included the presence of HIV infection ( P = 0.01) and duration of HIV infection ( P = 0.05). Variables associated with heart failure among PWH included older age, hypertension and myocardial infarction. Conclusions: No association between methamphetamine abuse/dependence and a diagnosis of myocardial infarction or heart failure was found among PWH. Significant covariates for myocardial infarction and heart failure included traditional risk factors, the presence of HIV infection and the duration of HIV infection, emphasizing the need for optimal traditional cardiovascular risk factor management among PWH.